Global meta‐analysis of soil‐disturbing vertebrates reveals strong effects on ecosystem patterns and processes. Issue 5 (18th January 2019) - Mallen‐Cooper, Max; Nakagawa, Shinichi; Eldridge, David J.
Abstract: Aim: Organisms that disturb the soil while foraging or creating shelter (ecosystem engineers) can have profound effects on ecosystems. Soil ejecta from these disturbances can enhance surface nutrients and the resulting depressions accrue organic matter and develop into biological hotspots. Here, we describe a global meta‐analysis of studies that assessed the impacts of vertebrate soil disturbance on both biotic and abiotic components of ecosystems. Location: Global land surface. Time period: 1941–2016. Major taxa studied: Vertebrates. Methods: After conducting a systematic literature search, we quantitatively synthesized the findings of 149 published studies that compared disturbed and undisturbed surfaces. Our meta‐analysis included 64 engineer species, primarily comprised of rodents and a subset of other mammals. Results: We found that vertebrate soil disturbance significantly enhanced soil nitrogen (by 77%) and phosphorus (35%), and the productivity (32%) and recruitment (32%) of vascular plants. Disturbances had a greater cover of bare soil (126%) than undisturbed controls, and higher abundances of secondary vertebrates (1, 233%), that use pre‐constructed burrows as shelter and foraging grounds. Soil disturbance significantly reduced water run‐off (63%) and the abundance of biocrusts (82%). Soil disturbance effects generally intensified with increasing aridity, and the magnitude of soil disturbance effects was not moderated by the area of the disturbance. Disturbances older than 12 months were more distinct from the surrounding matrix than fresh disturbances. The phylogeny of engineers was unrelated to their ecosystem effects, indicating that the same functionality could readily evolve in different taxa. Main conclusions: In general, disturbances become localized patches of elevated functioning, providing strong evidence that vertebrate engineers, especially those in drylands, are an important source of environmental heterogeneity.